Advanced exergy analysis of a PEM fuel cell with hydrogen energy storage integrated with organic Rankine cycle for electricity generation. (June 2022) - Montazerinejad, H.; Fakhimi, E.; Ghandehariun, S.; Ahmadi, P.
Abstract: In this study, a system consisting of PEMFC and ORC is modeled and analyzed from the thermodynamic aspects. Accordingly, to have a better understanding of the performance of the system, advanced exergy analysis is applied. The analysis is developed in Intel Fortran Compiler within the Microsoft Visual Studio. For modeling all dependent components, separate subroutines in the Microsoft Visual Studio platform were made by implementing the first and second law of thermodynamics. Based on the conventional exergy destruction rate, for the hybrid power system, Ėx, D, total is 484.4 kW. The results show that the exergy destruction rate in the PEMFC stack is the highest among other elements. The PEM fuel cell exergy efficiency is 46.89% according to the conventional exergy study. Moreover, the PEM fuel cell and overall electrical efficiencies are 39.06% and 44.81%, respectively. According to the advanced exergy analysis, except for the condenser and compressor, the avoidable part of exergy destruction rates is higher than those unavoidable. The largest endogenous and exogenous exergy destruction rates belong to PEMFC and compressor correspondingly. In addition, the compressor has a poor performance since its endogenous exergy destruction is 34.24 kW, and its unavoidable one is 19.55 kW. Besides, a large portion of its unavoidable (i.e., 57.09%) cannot be wiped out even we use the best technology. Moreover, the enhancement of components performance breeds eliminating the percentage of exogenous available exergy destruction rate of the turbine (57.66%) with the highest value. In the present work, the parametric study is conducted by increasing the current density as an essential design parameter to analyze its effects on some critical parameters such as the overall efficiency, the net generated power, and so on. For implementing the parametric study, the Engineering Equation Solver (EES) was used. The combination of Fortran and EES helped to obtain the required outcomes from the overall system. Besides, the overall efficiency increases until it reaches a maximum value of 47.31%and drops thereafter.